-x-1=3x-2

Simple and best practice solution for -x-1=3x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-1=3x-2 equation:


Simplifying
-1x + -1 = 3x + -2

Reorder the terms:
-1 + -1x = 3x + -2

Reorder the terms:
-1 + -1x = -2 + 3x

Solving
-1 + -1x = -2 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-1 + -1x + -3x = -2 + 3x + -3x

Combine like terms: -1x + -3x = -4x
-1 + -4x = -2 + 3x + -3x

Combine like terms: 3x + -3x = 0
-1 + -4x = -2 + 0
-1 + -4x = -2

Add '1' to each side of the equation.
-1 + 1 + -4x = -2 + 1

Combine like terms: -1 + 1 = 0
0 + -4x = -2 + 1
-4x = -2 + 1

Combine like terms: -2 + 1 = -1
-4x = -1

Divide each side by '-4'.
x = 0.25

Simplifying
x = 0.25

See similar equations:

| p/4=-1and1/6 | | Y+2x-12=180 | | 1/2(4a-16)=6 | | 3x^2-16x-60=0 | | p4=-1-1/6 | | (1.4)+(-2.3)= | | 7(1-8x)=175 | | x^2+13x+42=6 | | 3x-5=9x-6 | | 6750/10000 | | 3750/10000 | | 6750/10,000=? | | 25x-2.375=10 | | v/6=-5/7 | | -2(x-5)=4*4 | | -23=4h-3 | | -100=x+20 | | 4x^2-21=-3x | | 7(x+2)-12=5(x+2)-12+16 | | 5-(-7)+2(-8)= | | 550-475= | | -5x+18=x+1 | | 9x^3-39x^2-27x+13=0 | | h=-16t^2+70+50 | | 10x+x=33 | | 13x+10x=9 | | 784/26/43 | | 2b+8=3b-2 | | C=19y+41 | | -x-1/2=2 | | 4(2-5y)+16=-76 | | 2x*30*7*100/39 |

Equations solver categories